Current Density and Heating Patterns in Organic Solar Cells Reproduced by Finite Element Modeling. Issue 3 (22nd March 2017) - Öttking, Rolf; Roesch, Roland; Fluhr, Daniel; Muhsin, Burhan; Schubert, Ulrich S.; Hoppe, Harald
Abstract : We developed a finite element model of a finger structure polymer solar cell in conventional architecture in order to investigate current pathways and dissipative power losses. The model is of purely resistive nature, as this is sufficient to describe the effects under consideration. The model simulations yield the spatial distribution of the current densities, potentials and the according dissipative losses. In particular, the current pathways are spread out from the entire length of the top contact towards the entire width of the ground contact, running along the electric potential gradient. On the other hand, current crowding appears at the foremost part of the top electrode, resulting in a respective concentration of the resistive loss in this vicinity. The overall behavior of the current, mostly steers the resistive behavior of the device and is a delicate consequence of the interplay between the individual layer properties, namely the resistivities and layer thicknesses in combination. All this provides a first step towards a detailed quantitative description of the losses, depending on the geometrical cell design. The dissipative loss, in turn, is the origin of heat, which is observable by lock‐in thermography experiments, which are aimed to be reproduced by simulation. Abstract : We report FEM simulations of a finger structure polymer solar cell in conventional architecture. Current pathways are spread out over the entire solar cell. The temperature maximum appears at the foremost part of the top electrode. The temperature distribution results show a remarkable agreement with the dark lock‐in thermography measurements (see figure). This enables tracing back sources of power loss in polymer solar cells.